The Correlation between Transformational Leadership Styles with Teacher's Performance in SMP Negeri 2 Medan - Hendri Fauza (BIRCU, 2020)
This study aims to determine the principal's transformational leadership style used by SMP Negeri 2 Medan and the Performance of Teachers. The population in this study were all teachers in SMP Negeri 2 Medan. As a sample taken the entire study population using total sampling techniques. From the results of the study note that there is a positive relationship between the principal's transformational leadership style with the performance of teachers in SMP Negeri 2 Medan in the amount of rxy = 0.471 > 0.266. So from the hypothesis test results above it can be said that there is a relationship between Work Motivation and Teacher Job Satisfaction in An-Nizam Islamic Elementary School, where robserve > rtable (0.471 > 0.266) hypothesis is accepted with the meaning Ha is accepted and Ho is rejected if r observe < rtable. This level of relationship is included in the Medium level relationship interval.